1995
DOI: 10.1046/j.1471-4159.1995.64062581.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dopamine Uptake in the Basolateral Amygdaloid Nucleus, Caudate‐Putamen, and Nucleus Accumbens of the Rat

Abstract: Regional differences in the kinetics and pharmacological inhibition of dopamine uptake were investigated with fast‐scan cyclic voltammetry in both the intact rat brain and a brain slice preparation. The regions compared were the basolateral amygdaloid nucleus, caudate‐putamen, and nucleus accumbens. The frequency dependence of dopamine efflux evoked in vivo by electrical stimulation of the medial forebrain bundle was evaluated by nonlinear curve fitting with a Michaelis‐Menten‐based kinetic model. The Km for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
152
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(184 citation statements)
references
References 40 publications
32
152
0
Order By: Relevance
“…3a). Release and uptake rate constants (Table 1) in each region are distinct as reported previously (Jones et al 1995). In the CP, the time to peak for a 24-pulse stimulation was 83 ± 7 ms, significantly less than the 340 ± 35 ms measured in the BAN (p < 0.01, n ¼ 4).…”
Section: Testing the Model In Vivosupporting
confidence: 80%
See 1 more Smart Citation
“…3a). Release and uptake rate constants (Table 1) in each region are distinct as reported previously (Jones et al 1995). In the CP, the time to peak for a 24-pulse stimulation was 83 ± 7 ms, significantly less than the 340 ± 35 ms measured in the BAN (p < 0.01, n ¼ 4).…”
Section: Testing the Model In Vivosupporting
confidence: 80%
“…The appropriate handling of the diffusional aspects allows more accurate estimation of the kinetic rate constants controlling release and uptake. Remarkably, our V max , K m and [DA] p values agree with results obtained by cyclic voltammetry at Nafioncoated electrodes (Jones et al 1995), which required correction by deconvolution of the time constant for permeation through the Nafion film. Future models incorporating depression and augmentation of dopamine release by factors such as terminal autoreceptor effects should provide even more elegant predictions of dopamine concentrations.…”
supporting
confidence: 88%
“…Furthermore, a control K m value (inversely related to the affinity of the transporter for its monoamine) of approximately 0.2 μM for DA and 5-HT at their respective transporters was used and V max , which is proportional to the number of monoamine transporters, was also determined. These assumptions are best suited for evaluating release and uptake in striatal regions where one-pulse stimulations are used and that have rapid uptake, but can also be used with multiple pulse stimulations in areas with low uptake rates such as amygdala or midbrain (Bunin et al, 1998;John et al, 2006;Jones et al, 1995a). The curve fitting algorithm, based on simplex minimization and goodness of fit, was described by a nonlinear regression coefficient (r) (Jones et al, 1995b).…”
Section: Discussionmentioning
confidence: 99%
“…The K m values of 0.16 μM DA at DAT and 0.17 μM 5-HT at SERT were used for CPu and SNr measurements, respectively (Bunin et al, 1998;Near et al, 1988;Shaskan and Snyder, 1970;Wu et al, 2001b). When pharmacological agents were used, the change in the current vs. time profile was evaluated as a change in apparent K m ; inhibition of DA or 5-HT uptake was reflected as an increase in apparent K m (John et al, 2006;Jones et al, 1995a). The drugs studied have previously been described to competitively inhibit monoamine transport Davies et al, 1993;Jones et al, 1995b;Krueger, 1990;Missale et al, 1985;Richelson and Pfenning, 1984;Schuldiner et al, 1993;Wu et al, 2001a; but see, e.g., Coyle and Snyder, 1969;Eshleman et al, 1999;McElvain and Schenk, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The deficits observed are likely to be related to dysfunctioning within the fronto-striatal system. For example, the SHR has an impaired release of DA in the prefrontal cortex, nucleus accumbens and caudate-putamen (Deutch and Roth 1990; Jones et al 1995;Myers et al 1981;Russell et al 1995Russell et al , 1998Russell et al , 2000bRussell 2000). Young male SHRs have an increased density of D 1 and D 5 receptors in the neostriatum and nucleus accumbens (Carey et al 1998), and a recent study by Li et al (2007) showed that SHRs show a reduced expression of the D 4 receptor gene in the PFC.…”
Section: Animal Models Of Adhdmentioning
confidence: 99%